COTS software integration for simulation optimization coupling: case of ARENA and CPLEX products. (3rd July 2019) - Borodin, Valeria; Bourtembourg, Jean; Hnaien, Faicel; Labadie, Nacima
ABSTRACT: This paper focuses on coupling of simulation and optimization techniques, both representing an integrated part of modern design and decision-making support tools in management sciences, industry, and engineering. After revealing the different possible connotations of the concept of simulation optimization coupling, we explicitly describe the integration of two commercial-off-the-shelf industry-standard software tools ARENA and CPLEX, respectively. In addition, the coupling of ARENA with the add-on OptQuest is also discussed, in order to highlight the distinction between two different manners of putting into complementarity simulation and optimization tools, namely simulation encapsulated into optimization and, vice-versa, optimization encapsulated into simulation.